Effect of educational breast cancer smartphone application on knowledge, health beliefs and breast self-examination practices among female undergraduate students at a college university in Saudi Arabia - Almutairi, Aeshah Hamdan M (2020)
Breast cancer is the most frequently diagnosed cancer and the leading cause of cancerous deaths among females worldwide. In Saudi Arabia, breast cancer (BC) is the leading cause of cancerous deaths among Saudi women. Early detection of breast cancer can play an important role in reducing cancer morbidity and mortality. Early detection could be promoted by increasing knowledge, and by minimizing barriers about breast cancer. Previous studies have shown low breast cancer awareness among young Saudi women. Web based and smartphone applications covering a wide range of health topics including healthy lifestyle, fitness, disease management, and public health are currently available across all app stores with over 70% of them targeted at health. The main objective of this study is to develop, implement and evaluate the effectiveness of the educational program on breast cancer through a smartphone application based on knowledge, breast self-examination practices and health beliefs related to breast cancer among female students in university colleges in Saudi Arabia. This study is comprised of two phases which are the development of an educational application and also the evaluation of the educational protocol through a randomized controlled trial (RCT) among female students. The first phase is based on the qualitative approach and through a panel of experts, the final version of the apps was prepared and validated. The second phase of the study was done through a randomized controlled trial (RCT) for the selection of the participants. All female students who fulfilled the study’s inclusion criteria were invited to participate in the study with the provision of the informed consent form. Baseline data were collected from 144 female students (72 from the intervention group and 72 from the control group). The research instruments which included components on knowledge, practices, health belief and technology acceptance were adapted and adopted based on the literature. Content and face validity, on the other hand, were assessed by a panel of experts, followed by a pilot study. The intervention module is composed of an educational program on breast cancer and was validated and developed using a smartphone application. The data were collected at baseline, one month, 3 months and six months after intervention for both groups. The descriptive and inferential statistics used were the two-way repeated measure ANOVA and Chi square test for data analysis purpose using the SPSS software version 24. The results of the two-way repeated measure ANOVA indicate that the level of knowledge in the intervention group significantly increased after using the application. According to these results, it was found that the frequency of selfexamination in the intervention group was (79.5%) in follow-up1 and increased to 86.3% in follow-up 2, which was significantly different from the control group (p<0.001). These results also showed that the effects of intervention on the level of health belief components (perceived seriousness, perceived susceptibility, perceived benefits, perceived barriers, confidence and health motivation) in the pre, post and follow-up tests in the intervention have increased significantly: perceived seriousness [3.23(SP 0.36), 3.65(SD 0.53), 3.71(SD 0.46), 372(SD 0.43), p<0.01], and perceived susceptibility [2.90(SD 0.29), 3.79(SD 0.34), 3.79(SD 0.35), 3.83(SD 0,35),p<0.01],and perceived benefits [2.83(SD 0.34), 3.66(SD 0.24), 3.72(SD 0.22), 3.87(SD 0.19),p<0.01] and perceived barriers [4.14(SD 0.29), 2.46(SD 0.32), 2.22(SD 0.39), 2.19(SD 0.40), p<0.01] and confidence [3.08(SD 0.37), 3.77(SD 0.31), 3.85(SD 0.31), 3.83(SD 0.22), p<0.01] and health motivation [2.94(SD 031), 3.86(SD 0.27), 3.99(SD 0.25), 3.97(SD 0.28), p<0.01]. Differences between the intervention and control group were also statistically significant in the post-test, follow-up1 and follow-up2 (p<0.05). The results for the technology acceptance components among students in the intervention group indicated that that the level of all components related to using provided application have significantly improved across time. The study concluded that educational breast cancer smartphone application was an effectiveness approach on improving the knowledge, breast self-examination practices and health belief components to breast cancer among female students. Based on the findings of this study, more intervention experiments are needed to be applied to workplaces, rural, urban and other areas. in addition, this app could be used in hospital/community health settings. It can also be used individually by the females to detect breast cancer without incurring great costs.